1979
DOI: 10.1182/blood.v54.4.928.bloodjournal544928
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactic dehydrogenase as a prognostic tool for non-Hodgkin lymphomas

Abstract: Serum LDH levels have been found to be significantly increased in non- Hodgkin lymphoma (NHL) patients, both histiocytic and lymphocytic. The duration of survival of NHL negatively correlates with the level of serum lactic dehydrogenase (LDH), and statistical analysis reveals that patients with lower levels of LDH have a longer survival rate than the patients with higher LDH activity, irrespective of their histologic classification. The analysis of the results by the Test for Trend in Prognosis allows us to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…Serum LDH levels also have momentous significance in cancer diagnosis due to tissue destruction caused by tumor growth . In general, serum LDH is usually elevated in hematopoietic malignancies such as Hodgkin's lymphoma (HL) and non‐Hodgkin's lymphoma (NHL) . Colgan et al found that surgical removal of the primary tumor resulted in a dramatic decrease in serum LDH levels within first week after surgery.…”
Section: Ldha As a Biomarker And Therpeutic Target For Cancermentioning
confidence: 99%
“…Serum LDH levels also have momentous significance in cancer diagnosis due to tissue destruction caused by tumor growth . In general, serum LDH is usually elevated in hematopoietic malignancies such as Hodgkin's lymphoma (HL) and non‐Hodgkin's lymphoma (NHL) . Colgan et al found that surgical removal of the primary tumor resulted in a dramatic decrease in serum LDH levels within first week after surgery.…”
Section: Ldha As a Biomarker And Therpeutic Target For Cancermentioning
confidence: 99%
“…As a general consideration, high levels of LDH are mostly found in heart, liver, erythrocytes, skeletal muscles and kidneys. Although high levels of LDH are known to be associated with poor prognosis in both children and adults with lymphoma [9,10,11], its significance in patients who had undergone alloHSCT still remains unclear. The analysis of pretransplant serum LDH is considerably easy and unexpensive method so, this might be used to show patients with high risk prior to the transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of serum LDH levels is a well‐known diagnostic tool in human oncology 4–10 and, occasionally, measurement of LDH levels failed to show specificity in human cancer patients. For instance, high LDH levels in melanoma patients do not necessarily indicate a more advanced disease, thereby possibly leading to false‐positive results if not cautiously interpreted during initial staging work‐up 34 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LDH is one of the most common enzymes used in cancer patients for prognostic purposes, as its increase reflects tumour burden and treatment response. Indeed, LDH is considered as an important prognostic marker in lymphoma, 4,5 leukaemia, 6,7 germ cell tumours 8 and melanoma, 9,10 among others. Interestingly, serum measurement of LDH also helps in differentiating cancer from benign neoplasia, including uterine leiomyosarcoma from leiomyoma 11 and ovarian carcinoma from benign epithelial ovarian tumours 12…”
Section: Introductionmentioning
confidence: 99%